Policy Brief No. 26 - The Dynamics of First Nations Migration Shaped by Socio-Economic Inequalities - Amorevieta-Gentil, Marilyn; Bourbeau, Robert; Robitaille, Norbert (Scholarship@Western, 2016)
Migration by First Nations people (both Registered and non-registered Indians) reflects inequalities between First Nation communities, and also between First Nations and the non-Aboriginal Canadian population, in terms of its nature, its intensity and its direction. Residential mobility, within the same community or urban centre, is the commonest form of migration among First Nations, while inter-provincial and international migration concerns a small minority of cases. The net effect of the migratory flows of Registered Indians is movement towards reserves rather than to other rural or urban areas. Improvement in living conditions and the feeling of belonging to a community are the commonest motives for Indian migration. Communities may benefit from or be disadvantaged by these origin-destination flows.